Structure of DNA Binding MYB Transcription Factor Protein (ScMYBAS1-3) from Sugarcane – Threading and Ab Initio Modelling - Prasad D.1,4, Prabu G.R.1,2,3; Theertha (Journal of Phytology, 2011)
The sugarcane (Saccharum officinarum) stress-related MYB transcription factor gene, ScMYBAS1-3 demonstrated induced response to water-deficit and salt stress in our previous study. In order to elucidate its sequence-to-structure-to-function paradigm, the putative three-dimensional structure of ScMYBAS1 was generated using threading assembly refinement (I-TASSER) server. Further, PROCHECK, Verify-3D, PROMOTIF and ProSA programs were used to test the quality of model and the scores were within the recommended intervals. The models shed valuable information necessary for future identification of DNA binding regions and the prediction of co-regulated stress induced genes by docking studies. Key words: I-TASSER; ScMYBAS1; Sugarcane; Water-deficit <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Prabu G.R. and D. Theertha Prasad. Structure of DNA Binding MYB Transcription Factor Protein (ScMYBAS1-3) from Sugarcane – Threading and Ab Initio Modelling. J Phytol 3/3 (2011) 77-82